DIFFICULTIES AMONG SECONDARY STUDENTS OF SMP MUHAMMADIYAH PLUS BATAM ON LISTENING COMPREHENSION - Leil Badrah Zaki; Arya Dita; Pandu Prasodjo (PROJECT (Professional Journal of English Education), 2024)
This study investigates students’ difficulties in listening comprehension while doing the listening test and learning the skill in the class. The research aimed to find out the difficulties that student faced in listening test and the problems when learned listening skill. The research used the Brownell method that provided a framework of listening skills that consist of 6 components, that is hearing, understanding, remembering, interpreting, evaluating, and responding. The subject of the study is junior high school students of SMP Muhammadiyah Plus Batam. This research used mix-method research that questionnaire and interview used as the instrument. The students took from all grades 9 in that school. 102 students will fill out the question in the questionnaire and 8 of 102 students will be chosen to have an interview. The result showed that the difficulties encountered by the students on listening comprehension are related to the listener, speaker, and external factor. Besides that, their learning process in the class also affect their improvement and understanding in listening. Students shame in the class and the method and media used in the learning process. In listening material, long spoken text is the most difficult with 46.83% agree. The factor related the listener, showed 53.95% agree that pronunciation is difficult. Besides that, accent has the highest percentage with 52.90% and for the listening comprehension in learning process, 41.18% students have a bad habits like cheating.